Pesan Dakwah Pada Rubrik Oase Depok Pos - Hakim, Arip Rahman; Ikhtiono, Gunawan (KOMUNIKA, 2021)
Oase rubric is a rubric that contains writings about the wisdom of the story of the prophet Muhammad SAW (Sirah Nabawiyah), Companions of the Prophet, and the like. In addition, the Oase Rubric also contains knowledge about religion ranging from issues of life and the Islamic way of life, which are studied in written form to attract readers and apply them in everyday life. The contents of the da'wah message in this rubric are the goal to be analysed by the author through the da'wah message delivered in creed, morals and sharia. Based on the statement above, the question arises: a. What are the da'wah messages shown in the Depok oasis rubric? What preaching message is more dominant in the Depok post oasis rubric? In this study, the authors used a content analysis method, using a qualitative approach. By analysing each paragraph, then put into several subcategories and examine the contents of the message contained therein. Of the 11 propaganda messages in the Depok Post Oase Rubric sample dated January 9, 2019, to May 27, 2019, all received propaganda messages that can not be separated from the message of Aqidah, Morals, and Sharia. In the form of an invitation, the researcher can conclude that the Oase news on Depok Pos contains messages of preaching in invitations, warnings and Sirah Nabawiyyah (Story of the Prophet). The more dominant among the three messages of preaching is the message of preaching Sharia, where there are five pages of preaching (news) and 48 paragraphs in it.AbstrakRubrik Oase adalah rubrik yang berisi tulisan-tulisan tentang hikmah kisah Nabi Muhammad SAW (Sirah Nabawiyah), Sahabat Nabi, dan sejenisnya. Selain itu, Rubrik Oase juga memuat pengetahuan tentang agama mulai dari masalah kehidupan dan pandangan hidup Islami yang dikaji dalam bentuk tulisan untuk menarik minat pembaca dan menerapkannya dalam kehidupan sehari-hari. Isi pesan dakwah dalam rubrik ini menjadi tujuan yang ingin dianalisis penulis melalui pesan dakwah yang disampaikan dalam kategori akidah, akhlak dan syariah. Berdasarkan pernyataan di atas, timbul pertanyaan: a. Apa saja pesan dakwah yang disampaikan dalam rubrik oasis depok? Pesan dakwah apa yang lebih dominan dalam rubrik depok post oasis? Dalam penelitian ini penulis menggunakan metode analisis isi, dengan menggunakan pendekatan kualitatif. Dengan menganalisis setiap paragraf kemudian dimasukkan ke dalam beberapa sub kategori dan menganalisis isi pesan yang terkandung di dalamnya. Dari 11 pesan dakwah dalam sampel Rubrik Oase Depok Post tanggal 9 Januari 2019 sampai dengan 27 Mei 2019 semuanya mendapatkan pesan dakwah yang tidak lepas dari pesan Aqidah, Akhlak, dan Syariah. Dalam bentuk ajakan, peneliti dapat menyimpulkan bahwa berita Oase di Depok Pos mengandung pesan dakwah berupa ajakan, peringatan dan Sirah Nabawiyyah. Yang lebih dominan diantara ketiga pesan dakwah tersebut adalah pesan dakwah Syariah dimana terdapat 5 halaman dakwah (berita), dan memuat 48 paragraf didalamnya.